WALCOM: Algorithms and Computation 7th International Workshop, WALCOM 2013, Kharagpur, India, February 14-16, 2013. Proceedings - Ghosh, Subir Kumar.; Tokuyama, Takeshi. (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 7th International Workshop on Algorithms and Computation, WALCOM 2013, held in Kharagpur, India, in February 2013. The 29 full papers presented were carefully reviewed and selected from 86 submissions. The papers are organized in topical sections on computational geometry, approximation and randomized algorithms, parallel and distributed computing, graph algorithms, complexity and bounds, and graph drawing.